A revised classification of the amphibian reproductive modes - Nunes-De-almeida, Carlos Henrique Luz; Haddad, Célio Fernando Batista [UNESP]; Toledo, Luís Felipe (My University, 2021)
Amphibian reproductive modes (RMs) have been extensively described and applied to amphibian biology stud-ies. However, due to new behavioural observations and past system inconsistencies we found it necessary to review the current classification and redefine the sets of characters which define amphibian RMs. We suggest the use of 11 characters that include phases from egg to early development (including or not including larval stages) and we do not include behavioural aspects that are in general hard to identify, such as parental care, except those related to feeding and incubation. Based on 2,171 amphibian species (roughly a fourth of the species known), we built a dichotomous tree with 74 different possible RMs for amphibians – almost twice the number of the previous classification categories. This system could pos-sibly be applied to other vertebrates as well and therefore facilitate comparisons across different taxa.
Keywords: Anura; Behaviour; Breeding biology; Caudata; Gymnophiona; Reproduction; Reproductive strategies